The intrasulcular application effect of bisphosphonate hydrogel toward osteoclast activity and relapse movement - Tita Ratya Utari; Ika Dewi Ana; Pinandi Sri Pudyani; Widya Asmara (Saudi Dental Journal)
Introduction: Orthodontic relapse occurs after orthodontic treatment and shifting of teeth to unfavorable positions. Bisphosphonates’ effects on bone resorption and relapse prevention have been extensively investigated. However, topical administration, which results in local effect, is still a problem. Objective: This study aimed to investigate the effect of risedronate with gelatin hydrogel as a carrier to prevent relapse movement by inhibiting osteoclast activity. Methods: Lower incisors of 75 guinea pigs were moved distally using an orthodontic appliance until ±3 mm length. Gelatin hydrogel was fabricated to obtain a semisolid controlled release of 250 (Bis-CR250) and 500 mmol/L risedronate (Bis-CR500) and then applied intrasulcularly into the mesial subperiosteal area of 50 guinea pigs (25 in each group) every 3 days; the rest were the control (Bis-CR000). After 14 days of stabilization, the apparatus was removed. The distance decrease between incisors and the osteoclast number with TRAP staining at 0, 3, 7, 14, and 21 days were measured. ANOVA was used to determine the differences among the different time and experimental groups. Results: Both treatments showed significantly less relapse movement compared to the control (p < 0.05) at 14 and 21 days. Bis-CR500 more effectively inhibited the relapse movement than Bis-CR250 on day 21, indicating a dose dependency in the inhibition. Both treatments showed less osteoclast numbers than control (p < 0.05). Conclusion: Controlled release of bisphosphonate risedronate with a topically administered gelatin hydrogel has shown to be effective in decreasing the tooth relapse movement and osteoclast activity.